Interplay between magnetism and transport in the CuCr1‐xTi1+xS4 thiospinel: evidence for a strong asymmetry between p‐ and n‐type transport. Issue 15 (12th May 2022) - Hébert, Sylvie; Lebedev, Oleg; Maignan, Antoine
Abstract: A series of SPS densified ceramics with five compositions of the CuCr1‐x Ti1+x S4 thiospinel has been synthesized, with x close to 0. Their structural characterization by transmission electron microscopy confirms the spinel cubic structure and coupled EDX analysis reveals a homogeneous cation distribution which content follows x. Interestingly, the transport properties as attested by Seebeck and Hall coefficient measurements demonstrate the existence of a sign change of the majority charge carriers near x=0. Moreover, values of electrical resistivity are found to be much lower and metallic for x<0 than for x>0, the latter showing a variable range hopping mechanism. When combined to the thermal conductivity values, this leads to asymmetric thermoelectric figure of merit ZT values at 700 K, near 0.2 and 0.01 for p and n type sides, respectively. These p and n type regimes are also characterized by different magnitudes of negative magnetoresistance, and moreover, by a change of sign of the magnetothermopower at low T, from positive for p type to negative for electron doped compositions. This study shows the existence of a correlation between charges and spins for both n and p types of the CuCr1‐x Ti1+x S4 thiospinel, leading to an unusual positive sign of magnetothermopower in the p type case. Abstract :